2014
DOI: 10.1016/j.siny.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic risks of prenatal ionizing radiation

Abstract: s u m m a r yThe risk of cancer in offspring who have been exposed to diagnostic X-ray procedures while in utero has been debated for 55 years. High doses at high dose rates to the embryo or fetus (e.g. >0.5 Gy) increase the risk of cancer. This has been demonstrated in human epidemiology studies as well as in mammalian animal studies. Most pregnant women exposed to diagnostic X-ray procedures or the diagnostic use of radionuclides receive doses to the embryo or fetus <0.1 Gy. The risk of cancer in offspring e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 73 publications
0
30
0
4
Order By: Relevance
“…10 Also, cohort studies, which are superior to case-control studies, have not shown increased leukemia risk. 17 The study of childhood leukemias correlated with background radiation 11 does not consider confounding factors such as breastfeeding. Small changes in the results from consideration of such factors could make the increased leukemias statistically insignificant.…”
Section: Rebuttal: Mohan Doss Phdmentioning
confidence: 99%
“…10 Also, cohort studies, which are superior to case-control studies, have not shown increased leukemia risk. 17 The study of childhood leukemias correlated with background radiation 11 does not consider confounding factors such as breastfeeding. Small changes in the results from consideration of such factors could make the increased leukemias statistically insignificant.…”
Section: Rebuttal: Mohan Doss Phdmentioning
confidence: 99%
“…The Cancer Genome Atlas project integrated copy number, RNA, methylation status and miRNA data from approximately 300–460 human breast cancer genomes for each breast cancer subtype (9). Breast cancers positive for ER have a distinct methylome profile compared to the more aggressive ER-negative cancers (47). Methylation is a key component of differentiation-associated patterns of transcription in normal development of the mammary gland (48).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous articles using the rat and mouse confirm the all-or-none phenomenon (Job et al 1935;Russell 1950Russell , 1954Hicks et al 1953;Wilson et al 1953b;Russell and Russell 1956;Brent 1960aBrent , 1970Brent , 1999Brent and Bolden 1967a, 1968Coppenger and Brown 1967;Friedberg et al 1973;Schlesinger and Brent 1978;Roux et al 1983;Mazur 1984;Jacquet et al 1995;Adam 2012;Brent 2014b). Many other investigators have confirmed these findings, including Kim et al (2001), indicating no increase in malformations or growth retardation in mice following 2 Gy (gamma rays) at a preimplantation stage.…”
Section: The All-or-none Phenomenonmentioning
confidence: 94%